Study of market potential of plant based medicine A study of Dengue and Malaria - Anirudh Bharadwaj M; Kishor Bhat (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2019)
Treatment of illnesses with plants and plant-based concentrates has been a vital piece of the tropical regions. With the progression of innovative work in medication, there has been an expansion in the consideration of plant-based concentrates and side-effects utilized in the treatment of numerous ailments, use of conventional medications for sicknesses are getting incorporated into present-day prescription technique alongside normal medicines. Every year inclusive, the treatment of dengue and Malaria consolidated expenses are around USD 20 Billion every year. This paper centers around the market potential in the plant-based treatment of Dengue and Malaria as the diverse plants utilized in the treatment are broadly well-known and are developed in nations like India, African nations, and Latin America. It additionally tosses light on the recent trends in dengue and Malaria, customary strategies for treatment, and Dengue in the present day.